2021
DOI: 10.3947/ic.2021.0024
|View full text |Cite
|
Sign up to set email alerts
|

Chest Computed Tomography Severity Score to Predict Adverse Outcomes of Patients with COVID-19

Abstract: Background The novel coronavirus disease 2019 (COVID-19) continues to wreak havoc worldwide. This study assessed the ability of chest computed tomography (CT) severity score (CSS) to predict intensive care unit (ICU) admission and mortality in patients with COVID-19 pneumonia. Materials and Methods A total of 192 consecutive patients with COVID-19 pneumonia aged more than 20 years and typical CT findings and reverse-transcription polymerase chain reaction positive admit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 28 publications
3
20
1
Order By: Relevance
“…Recent reports show results compatible with our study as Hajiahmadi and colleagues reported ROC curve AUC 0.764 for CTSS1 for predicting severe/critical disease in a cohort including 24% severe/critical disease patients [ 27 ], while our calculated figure was 0.79. In addition, Aminzadeh and co-workers used a CTSS method similar to our CTSS7 and reported ROC curve AUC of 0.65 for triage of severe/critical patients and 0.76 for predicting critical disease at peak disease severity [ 28 ], while our corresponding calculated values for CTSS7 were 0.69 and 0.77, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Recent reports show results compatible with our study as Hajiahmadi and colleagues reported ROC curve AUC 0.764 for CTSS1 for predicting severe/critical disease in a cohort including 24% severe/critical disease patients [ 27 ], while our calculated figure was 0.79. In addition, Aminzadeh and co-workers used a CTSS method similar to our CTSS7 and reported ROC curve AUC of 0.65 for triage of severe/critical patients and 0.76 for predicting critical disease at peak disease severity [ 28 ], while our corresponding calculated values for CTSS7 were 0.69 and 0.77, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…The range of age in this study sample was 20–90 years with mean equals 52.51+/−13.56. Haji Ahmadi et al found significant increase in the ICU admission and mortality with increasing age, decreasing O2 saturation in patients with COVID-19 pneumonia [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zheng Ye et al [ 9 ] and Haji Ahmadi et al [ 7 ] stated that most of the cases showed lower lobar predominance. This was in contrast to what was stated in the current work that absent cranio-caudal predominance was the most common pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were also observed in several countries. 10 , 11 , 12 , 13 , 14 These studies suggest that the patients with higher CT-SSs might have more severe clinical outcomes and are more susceptible to mortality. Determination of the appropriate classification cut-off for this prognostic factor could have a considerable role in the early diagnosis and management of patients with poor prognoses.…”
mentioning
confidence: 93%